APPLICATION OF DOMINO CARD MEDIA TO INCREASE LEARNING ACTIVITY AT ELEMENTARY SCHOOL - Habsah, Ilvia; Habiby, M. Nuril Anwar; Suwasananingtyas, Suwasananingtyas (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2024)
This research is motivated of low activity students in learning . To overcome the problem of low activity, it is necessary to take action  to increase the learning activity of Class VB SDN Gadang 4 Malang 2023/2024 using Domino Card media. The research subjects to the action  students. Class VB with 28 students, the subject of the action is the student. The data collection method uses observation. The data analysis technique used classroom action research . The results of the siklus research showed that the average result of student activity in siklus I was 43.39%, while in siklus II the percentage was 61.61% and increased again to 80.18% in siklus III. And then, it can be concluded that the use of Card media can increase students' learning activeness, material about the parts of the eye and their functions for Class VB students at SDN Gadang 4 Malang.